A model‐based approach for the evaluation of once daily dosing of lamivudine in HIV‐infected children. (May 2014) - Piana, Chiara; Zhao, Wei; Adkison, Kimberly; Burger, David; Jacqz‐Aigrain, Evelyne; Danhof, Meindert; Della Pasqua, Oscar
<x xml:space="preserve">Abstract</x> Aim Little attention has been paid to the effects of compliance and prescription practice on treatment outcome in HIV‐infected children. In this context, an evaluation of the role of covariates on pharmacokinetics is required to establish the impact of differences in dosing regimens. Here we investigate whether a once daily dosing regimen of lamivudine provides comparable exposure to the currently approved paediatric regimen. Methods A hypothetical group of 180 patients between 3 months and 12 years old was used to evaluate the impact of body weight on systemic exposure to lamivudine. Simulation scenarios were evaluated using AUC and Cmax as parameters of interest. The analysis was performed using a population pharmacokinetic model previously implemented in nonmem v.6.2. Results The simulations show that once daily dosing of lamivudine yields comparable exposure to historical values observed in children and adults, both for liquid and solid dosage forms. Simulated steady‐state AUC(0–24 h) and Cmax values after once daily doses ranged respectively from 9.95 mg l−1 h and 1.9 mg l−1 for children lighter than 14 kg to 13.75 mg l−1 h and 3.0 mg l−1 for children heavier than 30 kg. These values are comparable or higher than historical values observed after once daily dosing in children and adults. Conclusions Our findings illustrate how dosing regimens can be evaluated taking into account the effects of developmental growth on drug disposition. Most importantly, they suggest that the reduction in dosing frequency to once daily leads to comparable lamivudine exposure, as observed after administration of a twice daily dosing regimen.